Application value of MRI-guided wire localization to the non-palpable breast lesions only shown in Breast MRI - Ma, Jiaqi; Hou, Leina; Liang, Xiufen; Yan, Bin; Dai, Qiang; Wang, Yunmei; Gao, Hongbian; Zhu, Jiang; Song, Canxu; Yuan, Quan (Frontiers in Oncology, 2024)
Magnetic resonance imaging (MRI)-guided wire localization can be applied to assist to remove suspected breast lesions accurately. This study aimed to evaluate the clinical application value of this technique in Chinese women. A total of 126 patients (131 lesions) who had underwent such technique in our hospital from April 2017 to December 2022 were enrolled. 1.5T MRI system and a wire localization device were used. Image characteristics, clinical features and postoperative pathology were collected and analyzed.All of 126 patients (131 lesions) were successfully localized by MRI and excised for biopsy. There were 39 malignant lesions (29.77%) and 92 benign lesions (70.23%). There was no significant correlation between the morphology of DCE-MRI and the ratio of malignant lesions (P=0.763), while there was a statistical correlation between the BPE, TIC curve and the malignancy rate (P<0.05). All the lesions were assessed according to BI-RADS category of MRI (C4A=77, C4B=40, C4C=12, C5=2). The malignancy raterates were as follows: 16.88% for 4A lesions (13/77), 37.50% for 4B lesions (15/40), 66.67% for 4C lesions (8/12) and 100% for 5 lesions (2/2). There was a significant correlation between the BI-RADS category and the incidence of benign-to-malignant lesions (P=0.000). MRI-guided wire localization can assist to remove suspected breast lesions early, safely and accurately. This technique makes up for the deficiency of X-ray and ultrasound, improves the accuracy of diagnosis and resection therapy in intraductal carcinoma and early invasive carcinoma, and helps to improve the prognosis of breast cancer.